Disruption of the microbiota across multiple body sites in critically ill children. Issue 1 (December 2016) - Rogers, Matthew; Firek, Brian; Shi, Min; Yeh, Andrew; Brower-Sinning, Rachel; Aveson, Victoria; Kohl, Brittany; Fabio, Anthony; Carcillo, Joseph; Morowitz, Michael
Abstract Background Despite intense interest in the links between the microbiome and human health, little has been written about dysbiosis among ICU patients. We characterized microbial diversity in samples from 37 children in a pediatric ICU (PICU). Standard measures of alpha and beta diversity were calculated, and results were compared with data from adult and pediatric reference datasets. Results Bacterial 16S rRNA gene sequences were analyzed from 71 total tongue swabs, 50 skin swabs, and 77 stool samples or rectal swabs. The mean age of the PICU patients was 2.9 years (range 1–9 years), and many were chronically ill children that had previously been hospitalized in the PICU. Relative to healthy adults and children, alpha diversity was decreased in PICU GI and tongue but not skin samples. Measures of beta diversity indicated differences in community membership at each body site between PICU, adult, and pediatric groups. Taxonomic alterations in the PICU included enrichment of gut pathogens such asEnterococcus andStaphylococcus at multiple body sites and depletion of commensals such asFaecalibacterium andRuminococcus from GI samples. Alpha and beta diversity were unstable over time in patients followed longitudinally. We observed the frequent presence of "dominant" pathogens in PICU samples at relative abundance >50%. PICU samples were characterized by loss of site specificity, with individual taxa commonly present simultaneously at three sample sites on a single individual. Some pathogens identified by culture of tracheal aspirates were commonly observed in skin samples from the same patient. Conclusions We conclude that the microbiota in critically ill children differs sharply from the microbiota of healthy children and adults. Acknowledgement of dysbiosis associated with critical illness could provide opportunities to modulate the microbiota with precision and thereby improve patient outcomes.